2021
DOI: 10.29023/alanyaakademik.879295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Artifical Intelligence on Human Resources Employees

Abstract: This research aims to reveal the effect of entrepreneurial tendencies of human resources employees on their individual performances and the mediating role of perception of towards change that AI can create. This research has been carried out with human resources employees of Turkey's largest second 500 companies in terms of capital. According to the results of the research, the entrepreneurial tendency of human resources employees significantly and positively affects their perception of towards change that AI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…This perception can directly affect the work performance of HR managers and employees. Kambur (2021) found that AI enables HR employees to be more entrepreneur-oriented and increases individual performance. Thus, AI is not perceived as a threat by the HR team.…”
Section: Discussionmentioning
confidence: 99%
“…This perception can directly affect the work performance of HR managers and employees. Kambur (2021) found that AI enables HR employees to be more entrepreneur-oriented and increases individual performance. Thus, AI is not perceived as a threat by the HR team.…”
Section: Discussionmentioning
confidence: 99%
“…Girişimcilik eğilimi, bir bireyin kendi işini yürütme arzusunu ve kararlılığını temsil eder. Girişimcilik eğilimi, bilinçli olarak ortaya çıkan bir davranış biçimidir (Kambur, 2021(Kambur, , s. 1480 ve kendi kaderini tayin etme, yenilikçilik, risk alma, proaktiflik ve rekabetçi bir yapı gibi temel süreçlerle birlikte bütününü oluşturmaktadır (Tiftik ve Zincirkıran, 2014, s. 182). Birçok araştırma, girişimci olmak için en önemli faktörün bireysel özellikler olduğunu göstermiştir.…”
Section: Girişimcilik Eğilimiunclassified
“…Two parts of business intelligence, managerial intelligence and equipment automation, are progressing quickly in tandem with the development of artificial intelligence technologies [1]. Human resource management is becoming an increasingly important part of management intelligence [2,3]. A company's ability to grow talent in the field of enterprise, improve management style, and increase total resource utilization is considerably aided by efficient human resource management.…”
Section: Introductionmentioning
confidence: 99%